Evolution of features of chronic pancreatitis during endoscopic ultrasound-based surveillance of individuals at high risk for pancreatic cancer - Konings, Ingrid C.A.W. (Endosc Int Open, 2018)
BACKGROUND AND STUDY AIMS : During endoscopic ultrasound (EUS)-based pancreatic ductal adenocarcinoma (PDAC)-surveillance in asymptomatic individuals, features of chronic pancreatitis (CP) are often detected. Little is known about the prevalence and progression of these features. The aim of this study was to quantify these features, assess the interobserver agreement, assess possible associated factors, and assess the natural course during 3 years of follow-up. PATIENTS AND METHODS : Two experienced endosonographers reviewed anonymized sequential EUS videos of participants in PDAC surveillance that were obtained in 2012 and 2015 for features of CP. Descriptives, agreement analyses, univariate and multivariate analyses for possible risk factors, and repeated measures analyses to assess intra-individual changes over time were performed. RESULTS : A total of 42 EUS videos of 21 participants were reviewed. Any feature of CP was present in 86 % (2012) and 81 % (2015) of participants, with a mean of 2.5 features per individual. The overall interobserver agreement was almost perfect at 83 %. No baseline factors were significantly associated with features of CP. Features did not change over time, except for hyperechoic foci without shadowing, which decreased intra-individually (β = – 1.6, P  = 0.005). CONCLUSIONS : This blinded study shows features of CP to be highly prevalent in individuals at high risk of developing pancreatic cancer. No baseline factors were associated with presence of these features. CP features did not increase intra-individually over a 3-year period. Longer follow-up and pathological examination of pancreatic resection specimens will be essential to learn whether EUS detection and follow-up of these CP features bear clinical relevance.